النظم البيئية الريادية للمؤسسات الناشئة -بالإشارة للجزائر- - بن مبارك، زهية; بن تربح ،بن تربح (جامعة الوادي University of Eloued, 2024)
ملخص: تستعرض هذه الورقة مفهوم النظام البيئي الريادي للمؤسسات الناشئة، وهذا من خلال مراجعة للتعارف المتعددة للنظم البيئية الريادية الموجودة في الأدبيات، وذلك من خلال استكشاف دور النظم البيئية الريادية في الشركات الناشئة في دفع التحول نحو الاقتصاد، ويمكن للشركات الناشئة أن تستفيد من الجهات الفاعلة الرئيسية في النظم البيئية الريادية، مثل الجامعات وحاضنات الأعمال ووسطاء تطوير المشاريع التي لها علاقة، وهذا أمر حيوي لدعم الشركات الناشئة، والزيادة من القدرة التنافسية للمشاريع الجديدة.مع الإشارة إلى النظام البيئي الريادي للمؤسسات الناشئة في الجزائر. تسلط نتائج البحث الضوء على أهمية دراسة النظام البيئي الريادي للمؤسسات الناشئة، وإبراز الترابط بين الجهات الفاعلة الرئيسية في النظام البيئي الريادي، ومحاولة لملء الفجوة من خلال استكشاف النظام البيئي لريادة الأعمال للشركات الناشئة في الجزائر، فرغم الاهتمام المتزايد بالنظم البيئية لريادة الأعمال، لا يزال هناك تحدي يتعلق بكيفية تكوينها وترابطها لخلق بيئة داعمة للمشاريع المبتكرة، التي تمكنها من توفير بيئة وخدمات داعمة لإنشاء النظام البيئي للشركات الناشئة في الجزائر فيما يتعلق بالتعاون بين الأعمال والحكومة. This paper explores the concept of the entrepreneurial ecosystem for startups, through a review of the multiple definitions of entrepreneurial ecosystems found in the literature. We explore the role of entrepreneurial ecosystems in startups in driving the transformation towards the economy, and startups can benefit from key actors in entrepreneurial ecosystems, such as universities, business incubators and relevant project development intermediaries, which is vital to support startups and increase the competitiveness of new projects. With reference to the entrepreneurial ecosystem for startups in Algeria. The research results highlight the importance of studying the entrepreneurial ecosystem for startups, highlighting the interconnectedness between the key actors in the entrepreneurial ecosystem, and attempting to fill the gap by exploring the entrepreneurial ecosystem for startups in Algeria. Despite the growing interest in entrepreneurial ecosystems, there is still a challenge related to how they are formed and interconnected to create a supportive environment for innovative projects, which enables them to provide a supportive environment and services for establishing the startup ecosystem in Algeria in terms of cooperation between business and government.
Entrepreneurial Ecosystems for Startups - with Reference to Algeria-
Keywords: نظام بيئي; ريادة الأعمال; مؤسسات ناشئة; نظام بيئي ريادي; دورة حياة النظام البيئي; Ecosystem; Entrepreneurship; Startups; Entrepreneurial Ecosystem; Ecosystem Lifecycle